Systematic review and meta-analysis of the efficacy and safety of vibegron vs antimuscarinic monotherapy for overactive bladder. Issue 5 (5th February 2021) - Su, Shunye; Liang, Liqin; Lin, Jinlei; Liu, Ludong; Chen, Zhipeng; Gao, Yuan
Abstract: Background: Vibegron is a new β3-adrenergic receptor agonist which has been demonstrated for the treatment of overactive bladder (OAB). We carried out meta-analysis to evaluate the efficiency of vibegron vs antimuscarinic monotherapy for treating OAB. Methods: Randomized controlled trials (RCTs) of Vibegron vs antimuscarinic monotherapy for OAB were searched systematically by using EMBASE, MEDLINE, and the Cochrane Controlled Trials Register. The RevMan version 5.3.0. was used to analysis the data. Results: Three RCTs involving a total of 1751 patients were studied in the Systematic review and Meta-analysis. Efficacy end points: the mean number of micturitions episodes/d ( P  = .16); the mean number of urgency episodes/d ( P  = .05); mean number of urgency incontinence episodes/d ( P  = .11) and mean number of incontinence episodes/d ( P  = .14) indicated that vibegron and antimuscarinic had no significant differences in terms of OAB treatment. Mean volume voided/micturition showed a distinct difference in the two groups ( P  = .009). With regard to dry mouth and drug related treatment-emergent adverse event (TEAE), vibegron showed better tolerance than antimuscarinic. Serious adverse event (SAE) and discontinuations due to adverse event (AE) did not show a significant difference between the two groups. Conclusions: The therapeutic effect of vibegron is similar to that of antimuscarinic, but vibegron does not increase the risk of AE.